The evolution of cell-free fetal DNA testing: expanded non-invasive prenatal testing and its effect on target populations - Yang, Shaozhe; He, Yanqi; Lv, Jingshang; Li, Rongxiang; Fu, Xiuhong (Frontiers in Medicine, 2025)
PurposeTo evaluate the clinical performance of expanded non-invasive prenatal testing (NIPT-plus) in screening for fetal chromosome aneuploidy and copy number variations (CNVs) among pregnant women with different risk factors to investigate how the target population of cell-free fetal DNA may change in NIPT-plus.MethodsThe clinical data, test results, confirmatory invasive testing outcomes, and follow-up results of 6,220 pregnant women who underwent NIPT-plus were re-viewed. The performance indicators of the positive predictive value (PPV), positive rate (PR), specificity, and sensitivity in screening for common trisomies, sex chromosomal abnormalities (SCAs), rare autosomal aneuploidies (RAAs), and CNVs were calculated. The PR or PPV of NIPT-plus for screening chromosome aneuploidy and CNVs in women of varying ages, risk factors, and clinical indications were determined.ResultsThe PRs of common trisomies, SCAs, RAAs, and CNVs in NIPT-plus were 0.71, 0.45, 0.32, and 0.59%, respectively, with 100% sensitivity and specificities ranging from 99.69 to 99.87%. The PPVs were 80.95, 30.77, 13.33, and 44.12%, respectively. The high-risk group had higher PRs and PPVs for chromosome aneuploidy, with no significant difference in screening for CNVs. NIPT-plus showed greater PR for aneuploidy in the older age group than in the younger age group, with no significant differences in CNVs screening.ConclusionNIPT-plus was able to effectively screen for chromosome aneuploidy and CNVs. The performance of CNVs screening was not significantly different among different risk factors and age groups. The target population for NIPT-plus should include all pregnant women, not just those at high risk.